A straightforward LC approach using an amine column and single quad mass detector to determine choline chloride in feed additives and feeds - Granados Chinchilla, Fabio (2017)
Considering choline (ChCl) as an essential ingredient for animals and that it is administered through feed, we developed an easy, accurate, and sensitive method for its analysis. The method is straightforward, derivatization-free and has no secondary chromatographic interactions. •We demonstrated that the method can be used for quality control for feeds and feed additives containing choline chloride, •We report a simple chromatographic method which takes advantage of the hydroxyl moiety present in ChCl and a MS detector. •We demonstrated that a single quadrupole detector is an effective option for the quantification of ChCl in feeds as an alternative for the more expensive tandem MS system.